Phantasien über Beethoven-Symphonien - Paunzen, Arthur, 1890-1940 (artist):::Creator:::::::::::: (Austria; R. Lányi; Vienna, 2022)
Beethoven portrait engraving with title for the series of allegorical etchings on Beethoven's symphonies.